Specific transcriptional responses to juvenile hormone and ecdysone in Drosophila. - Beckstead, R.B.; Lam, G.; Thummel, C.S. (Insect Biochemistry and Molecular Biology, 2007)
Previous studies have shown that ecdysone (E), and its immediate downstream product 20-hydroxyecdysone (20E), can have different biological functions in insects, suggesting that E acts as a distinct hormone. Here, we use Drosophila larval organ culture in combination with microarray technology to identify genes that are transcriptionally regulated by E, but which show little or no response to 20E. These genes are coordinately expressed for a brief temporal interval at the onset of metamorphosis, suggesting that E acts together with 20E to direct puparium formation. We also show that E74B, pepck, and CG14949 can be induced by juvenile hormone III (JH III) in organ culture, and that CG14949 can be induced by JH independently of protein synthesis. In contrast, E74A and E75A show no response to JH in this system. These studies demonstrate that larval organ culture can be used to identify Drosophila genes that are regulated by hormones other than 20E, and provide a basis for studying crosstalk between multiple hormone signaling pathways.